Pembuatan Minyak Kelapa Murni (Virgin Coconut Oil) dengan Metode Fermentasi dan Optimasi Waktu Simpan dan Penjernihan Menggunakan Ekstrak Daun Lada dan Karbon Aktif - Pornawati, Heni; Aldila, Herman; Aprilianti, Rena; Selviani, Dera (Jurusan Fisika, Universitas Bangka Belitung, 2023)
Coconut oil is a valuable part of the coconut fruit and is widely used as an industrial raw material or part of it is made into cooking oil. Oil extraction from coconut meat can be done in several ways. Extraction of coconut oil that is being developed at this time is the fermentation method using several enzymes or microbes, one of which can be used is yeast tempeh. This research aims to analyze the yield content and quality criteria of coconut oil made using the fermentation method and to analyze the effect of adding pepper leaf extract and activated carbon on the shelf life and clarification of coconut oil. From the results of experiments carried out in mixing tempeh yeast, the free fatty acid test, yield test, aroma test and density test were carried out. As for the test results, the determination of free fatty acids in this cooking oil study used the titration method with NaOH until the color changed to pink. For the redemption test, the highest oil concentration was 3 grams, while the tempeh yeast 4 grams and 5 grams decreased. Aroma test where in week 9 coconut oil without treatment experienced rancidity. This was caused by auto-oxidation which began to form radicals due to the presence of fat peroxidation factors. The density test is close to the SNI standard value, namely the lowest density of 0.9600 g/cm3 obtained from closed treatment with 0.5 ml of extract. This is because in this treatment very little cooking oil is contaminated with other substances.